Women credit activities in a rural town in Bohemia in the 18th century: The case of Lidmila Löschová - Jan Lhoták (The Journal of European Economic History (JEEH), 2022)
The role of widows in the artisan-agrarian urban society in East-Central Europe was usually narrowed down to the position of provisional manager of the bequeathed property until a male heir reached adulthood. However, some individual stories show us that women often times were also very capable and active businesswomen. One of such individuals was Lidmila Löschová, the daughter of a suburban miller in the Czech royal town of Suésice. For her, marriage to a middle-class burgher meant a horizontal social shift from inhabitant of the suburbs to the urban middle class. Having been early wid- owed, she took up economic activities in which she by far surpassed not only her husband, but also her male counterparts operating in the same business branch. By skilfully trading grain, she became the most important grain handler both in town and in the entire surrounding region; she provided loans to both the urban and rural population and invested the acquired capital in properties which she then used for speculations, expanding her assets even further. The inheritance file, which captures her activities and economic re- lationships, is the most extensive fascicle of its kind in the town archive and it is the best documentation of this remarkable woman's extraordinary fate.
Keywords: 330; Women entrepreneurs; Credit business; Grain trade; Bohemia; Unternehmerinnen; Kreditgeschäft; Getreidehandel; Böhmen